THE HISTORICAL-CRITICAL PERSPECTIVE OF INTEGRAL EDUCATION: MORE THAN JUST TO EXTEND THE SCHOOL TIME - Elaine Cristina Melo Duarte; Mara Regina Martins Jacomeli (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
This paper works on contributions of Historical Critical Pedagogy and Marxism to the concept of integral education making a comparing them with the education policies in Brazil. Sometimes the official educational programs in Brazil don't make a clear distinction between integral education and full-time education. In order to improve the results of evaluations of public educational systems in Brazil, the government is extending the daily school time. However, the causes of the insufficient results obtained by the schools in evaluations are considered external to the pedagogical practice and the extension of daily school time is not organized with the aim to improve the learning of school contents. Instead of this, the extra time has been utilized for activities organized with the intention to solve extra-escolar social problems or just recreational activities. The result is not a better learning of school knowledge but, instead of that, at the end of the journey, the pupils didn't have time to do their homework. The historical critical perspective disagrees of this misconception of integral education and defends pedagogical measures in order to improve the teaching and the learning of school knowledge. Keywords: Integral Education. Full Time Education. Historical Critical Pedagogy.